Business models for interoperable mobility services - Vincent A.C. van den Berg; Henk Meurs; Erik T. Verhoef (Tinbergen Institute, 2020)
Travelers often combine transport services from different firms to form trip chains: e.g. first train and then a bus. Integration of different forms of public and private transport into a single service is gaining attention with the concept of Mobility as a Service (MaaS). Usually, the focus is on such things as ease of use, and shifting demand away from the car. We solely focus on the effects on behaviour and welfare via the market structure of transport. In particular, we analyse three archetype ways in which MaaS could be operationalized: Integrator, Platform, and Intermediary. We find that these models differ strongly in how consumers and firms are affected. The Integrator seems best for consumers and social welfare. It always leads to lower prices than Free Competition without Maas and therefore benefits consumers; transport firm profits can be lower or higher. The Platform tends to lead to an outcome that is relatively close to Free Competition without Maas: prices can be higher or lower, while transport firm profits are lower. Finally, the Intermediary tends to lead to much higher prices. Regulation of the price that the MaaS firm has to pay may further lower prices, but compared to the Integrator the difference is often small. So, even without price regulation, MaaS supply can already benefit consumers by increasing competition and removing serial marginalization, even before we consider other benefits of MaaS such as information provision, ease of use and a demand shift towards public transport.
Keywords: R40; D21; D43; 330; MaaS; market structure; platform; intermediary; integrator; regulation